2001
DOI: 10.1002/mrm.1208
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan‐induced changes in T‐relaxation of articular cartilage at 4T

Abstract: Proteoglycan (PG) depletion-induced changes in T 1 (spin-lattice relaxation in rotating frame) relaxation and dispersion in articular cartilage were studied at 4T. Using a spin-lock cluster pre-encoded fast spin echo sequence, T 1 maps of healthy bovine specimens and specimens that were subjected to PG depletion were computed at varying spin-lock frequencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
345
2
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 358 publications
(366 citation statements)
references
References 33 publications
(33 reference statements)
18
345
2
1
Order By: Relevance
“…However, except for a constant shift, there were no significant changes observed in the T 1r dispersion curve with varying levels of GAG depletion by trypsin (25). Discrepancy between these results may be due to the measurement of global (spectroscopic) vs (imaging) regional T 1r and difference in static field strength.…”
Section: T 1r Dispersion In Cartilagementioning
confidence: 79%
See 2 more Smart Citations
“…However, except for a constant shift, there were no significant changes observed in the T 1r dispersion curve with varying levels of GAG depletion by trypsin (25). Discrepancy between these results may be due to the measurement of global (spectroscopic) vs (imaging) regional T 1r and difference in static field strength.…”
Section: T 1r Dispersion In Cartilagementioning
confidence: 79%
“…Prominent in these are: proton-based methods such as T 2 relaxation mapping (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), delayed gadoliniumenhanced magnetic resonance imaging contrast (dGEM-RIC) (21,22), T 1r relaxation mapping (23)(24)(25)(26) and the direct MRI of sodium (27)(28)(29)(30). T 2 is predominantly affected by changes in collagen content and to a smaller extent in PG in the tissue.…”
Section: Osteoarthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Since PG loss is an initiating event of OA, the ability to noninvasively quantitate PG changes may be useful for making an early diagnosis, monitoring response to therapy, assessing the efficacy of cartilage repair, and conducting longitudinal follow-up studies. Different magnetic resonance imaging (MRI) techniques have been proposed to quantify early biochemical changes in cartilage, particularly PG changes (1)(2)(3)(4)(5)(6)(7)(8). Although MRI can detect cartilage fibrillation more accurately than other diagnostic techniques, conventional MRI techniques are insensitive in detecting early changes in OA.…”
mentioning
confidence: 99%
“…Recent in vitro and in vivo studies on cartilage have demonstrated that the T 1 is sensitive to changes in the PG content of cartilage (7,8,21). In a study of bovine cartilage it was shown that the T 1 relaxation rate changes linearly with changes in the PG content of cartilage (6). It was also reported that spin-lock MRI (22) eliminates residual dipolar interaction (RDI) in cartilage as long as the amplitude of the spin-lock pulse is greater than the RDI.…”
mentioning
confidence: 99%